Industri Pariwisata dan Ekonomi Kreatif di Dusun Pancot, Keluruhan Kalisoro, Tawangmangu - Haryatno, Yulius Rudi; Nugroho, Suryo; Edy, Irwan Christanto (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
The aim of this community service activity is to provide knowledge and motivation for tourist village communities and local stakeholders to enter the world of the tourism industry. This is important to do so that the tourism potential in rural areas truly brings blessings to the local community, not to corporations. The way rural communities